2015
DOI: 10.1007/s10725-015-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of amylopectin structure and activities of key starch synthesis enzymes in the grains of rice single-segment substitution lines with different Wx alleles

Abstract: The Wx gene is the major gene controlling amylose synthesis in rice endosperm. So far, the Wx gene can be mainly classified into five common alleles, wx, Wx t , Wx g1 , Wx g2 , and Wx g3 , according to their amylose phenotypes. Besides, the Wx allelic variation was also found to play an important role in regulating other physicochemical properties of rice starch. However, the specific physiological and starch structural mechanisms are not clear yet. With a set of singlesegment substitution lines harboring five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The reason that the Wx g1 and Wx g2 genotype starches showed similar RC values may be attributed to their differences in amylopectin structure. Compared with the Wx g1 genotype starch, the Wx g2 starch was found to have a higher proportion of medium‐length chains (degree of polymerization, 28–67) in amylopectin, which may have the ability to form more stable double helices and therefore compensate for the reduction in RC caused by the AAC variation.…”
Section: Resultsmentioning
confidence: 96%
“…The reason that the Wx g1 and Wx g2 genotype starches showed similar RC values may be attributed to their differences in amylopectin structure. Compared with the Wx g1 genotype starch, the Wx g2 starch was found to have a higher proportion of medium‐length chains (degree of polymerization, 28–67) in amylopectin, which may have the ability to form more stable double helices and therefore compensate for the reduction in RC caused by the AAC variation.…”
Section: Resultsmentioning
confidence: 96%
“…However, previous research reported that gene allelic variation will affect the activity of the corresponding enzyme. 29,30 In order to investigate whether these amino acid variations will lead to a difference in enzyme activity, the recombinant plasmids with the above genes from strain Y-2 or W-21 were constructed, and electro-transformed into B. subtilis 168 competent cells. Consistent with the expected molecular mass of the corresponding enzyme, the thick protein band that appeared when SDS-PAGE was performed was observed in the cell-free extracts from strains carrying the recombinant plasmid (data not shown).…”
Section: Analysis Of Enzymes Activitymentioning
confidence: 99%
“…The rest of the homogenate was centrifuged at 10,000 g for 15 min, and the supernatant was used for the determination of SS, ADPG, SBE, and DBE activities ( Dai, 2010 ). UDPG and SSS were determined according to the method of ( Teng et al., 2015 ). All parameters were measured four times.…”
Section: Methodsmentioning
confidence: 99%